Enhancement effect of heat recovery on hydrogen production from catalytic partial oxidation of methane - Chen, Wei-Hsin; Chiu, Ting-Wei; Hung, Chen-I. (International journal of hydrogen energy, 2010)
The effect of heat recovery on hydrogen production from catalytic partial oxidation of methane (CPOM) and its reaction characteristics in a reactor are investigated using numerical simulations. The reactor is featured by a Swiss-roll structure in which a rhodium (Rh) catalyst bed is embedded at the center of the reactor. By recovering the waste heat from the product gas to preheat the reactants, it is found that the combustion, steam reforming and dry reforming of methane in the catalyst bed are enhanced to a great extent. As a result, the methane conversion and hydrogen yield are improved more than 10%. Considering the operation conditions, a high performance of hydrogen production from CPOM can be achieved if the number of turns in the reactor is increased or the gas hourly space velocity (GHSV) of the reactants in the catalyst bed is lower. However, with the condition of heat recovery, the flow direction of the reactants in the reactor almost plays no part in affecting the performance of CPOM. In summary, the predictions reveal that the reactor with a Swiss-roll structure can be applied for implementing CPOM with high yield of hydrogen.